Development and assessment offluorinated grapheme nanoparticles modified dental adhesives (Medico Legal Update, 2020)
Background: The success of adhesion to the tooth structure plays an important role in the dental restoration,which can effectively avoid the terrible clinical problems during the bonding process, including the secondarycaries and the loading of adhesive compositions with fillers and nanoparticles with antibacterial propertieshas led to a significant reinforcement effect of the adhesive.Objective: The current study is designed to investigate the effects of addition of 2% of fluorinated grapheneon the adhesive-dentin hybrid layer for two types of commercially available universal adhesive, guidedusing the etch and rinse technique as a bonding procedure.Method: Forty extracted premolar teeth will be divided into four groups of ten teeth. Group I: the nonincorporated (Prime & Bond Universal) bonding agent (Control group). Group II:using the 2% FGnanoparticles incorporated (Prime & Bond Universal) bonding agent. Group III: non-incorporated (AllBond Universal) bonding agent (Control group). Group IV: using the incorporated (All Bond Universal)bonding agent. The degree of conversion was also measured using Fourier transform infrared spectroscopy(FTIR). The antibacterial activity of the adhesives was evaluated using agar diffusion test against thefollowing bacteria: Streptococcus mutans and Lactobacillus salivarius obtained from saliva.Results: A significantly greater antibacterial activity was obtained with adhesives containing a 2% fluorinatedgrap hene nanoparticles than other groups (P